14 days of intermittent hypoxia does not alter haematological parameters amongst endurance trained athletes - Clark, S. A.; Dixon, J.; Gore, C. J.; Hahn, A. G. (Proceedings from the Gatorade International Triathlon Science II Conference, Noosa, Australia, November 7-8, 1999: Maximising Olympic Distance Triathlon Performance: A multi-disciplinary perspective, 1999)
The aim of this study was to determine the efficacy of intermittent hypoxic therapy on red cell production amongst a group of well trained athletes. Eight rowers underwent preliminary testing and were pair matched for VO2max and performance on a rowing ergometer. In a single blind design, with both groups sitting quietly at rest, the treatment group (TRE) inhaled 12.20% O2 while the control group (CON) inhaled 20.93% O2. The groups inhaled gas for 5 min and then room air for 5 min alternately for a total of 90 min.d-1 for 14d. The performance test was conducted twice before and twice after 14d of IHT. A venous blood sample was taken at rest before and immediately after IHT. During IHT there was a decrease in SpO2 (p<0.05) and increase in HR (p=0.06) in the TRE compared with the CON. There was no change in resting values for RBC, [Hb], Hct and reticulocytes between pre and post measurements for either the TRE or CON group. During the performance test there were no differences for HR, submaximal VO2, VO2max, total metres, La and respiratory exchange ratio. In conclusion, IHT of 90 min.d-1 for 14 d had no effect on any haematological parameters which would reflect an increase in total haemoglobin mass and accordingly there was no effect on VO2max or ergometer performance.